2015
DOI: 10.1051/0004-6361/201425372
|View full text |Cite
|
Sign up to set email alerts
|

The evolved circumbinary disk of AC Herculis: a radiative transfer, interferometric, and mineralogical study

Abstract: Context. Many post-asymptotic giant branch (post-AGB) stars in binary systems have an infrared (IR) excess arising from a dusty circumbinary disk. The disk formation, current structure, and further evolution are, however, poorly understood. Aims. We aim to constrain the structure of the circumstellar material around the post-AGB binary and RV Tauri pulsator AC Her. We want to constrain the spatial distribution of the amorphous and of the crystalline dust. Methods. We present very high-quality mid-IR interferom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 74 publications
4
88
0
Order By: Relevance
“…Another good recently studied example of an evolved disc is AC Her (Hillen et al 2015) whose interfermetric measurements show that the inner radius of the disc is large, the large grains have been settled to the midplane and the gas/dust ratio is small. Interestingly also BD+33 • 2642, the central star of the PN G052.7+50.7 was found to be a depleted (Napiwotzki et al 1994) and recently found to be a binary as well .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another good recently studied example of an evolved disc is AC Her (Hillen et al 2015) whose interfermetric measurements show that the inner radius of the disc is large, the large grains have been settled to the midplane and the gas/dust ratio is small. Interestingly also BD+33 • 2642, the central star of the PN G052.7+50.7 was found to be a depleted (Napiwotzki et al 1994) and recently found to be a binary as well .…”
Section: Discussionmentioning
confidence: 99%
“…Also the dust component in these two objects was presumed to be C-rich. Both assertions are, however, no longer supported by more recent works, like the photospheric abundance analysis of Van Winckel et al (1998) and the dust studies of , , , Gielen et al (2007Gielen et al ( , 2009 ;Hillen et al (2015). One exception may be V453 Oph, which shows a mild s-process overabundance but it is not accompanied by C enhancement (Deroo et al 2005).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this case the blackbody model that we fit to the infrared data would represent emission from the inner circumbinary disk, while the redder 5.8 and 8.0 μm excess is likely emanating from the outer portion of the circumbinary disk as lowertemperature blackbody emission. The four IRAC data points that compose the IR excess in HoIX X-1 are not sufficient to fit a complicated circumbinary disk model (e.g., Akeson et al 2007;Hillen et al 2015); however, in its simplest form, the circumbinary disk model is very similar to an irradiated disk model, only the source of illumination in the former case is the accretion disk and the star. We therefore fit a very simple p-free disk model to the four IRAC points.…”
Section: Origin Of the Ir Emission In Holmberg IX X-1mentioning
confidence: 99%
“…Disks with gaps or large inner holes have depressed near-to mid-IR fluxes (as is the case for AC Her, Hillen et al (2015)). …”
Section: Results Of the N Band Interferometric Surveymentioning
confidence: 93%